2010
DOI: 10.1155/2010/864817
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Screening of 24 Target Genes of Foodborne Pathogens in 35 Foodborne Outbreaks Using Multiplex Real-Time SYBR Green PCR Analysis

Abstract: A set of 8 multiplex real-time SYBR Green PCR (SG-PCR) assays including 3 target primers and an internal amplification control (IAC) primer was simultaneously evaluated in 3 h or less with regard to detection of 24 target genes of 23 foodborne pathogens in 7 stool specimens of foodborne outbreak using a 96-well reaction plate. This assay, combined with DNA extraction (QIAamp DNA Stool Mini kit), offered detection of greater than 103-104 foodborne pathogens per g in stool specimens. The products formed were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…In addition, we determined the LOD of the real-time PCR assay using the DAPM and the QIAamp DNA Stool Mini Kit (Qiagen, Hilden, Germany), which is commonly used to extract and purify DNA with a column from stool samples (10)(11)(12). Then, the 2 LODs were compared.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we determined the LOD of the real-time PCR assay using the DAPM and the QIAamp DNA Stool Mini Kit (Qiagen, Hilden, Germany), which is commonly used to extract and purify DNA with a column from stool samples (10)(11)(12). Then, the 2 LODs were compared.…”
Section: Methodsmentioning
confidence: 99%
“…Although real-time polymerase chain reaction (PCR) assays detect viral pathogens within a few hours, bacterial culture methods (BCs), used to identify the causative pathogen, are time-consuming and laborious (3-7 days) (4-6). We developed a SYBR Green I-multiplex real-time PCR (SG-mPCR) screening system that simultaneously (within 3.5-4 h) analyzes 6 types of diarrheagenic Escherichia coli and 15 bacterial foodborne pathogens (1,7). This screening system, designated as Rapid Foodborne Bacterial Screening 24 (RFBS24 ver.5) includes 8 sets (Sets A-H) of SG-mPCR assays, each comprised of 6-7 primers for 3 genes and a competitive internal amplification control (IAC).…”
Section: Introductionmentioning
confidence: 99%
“…Fukushima et al (6) described an expedited screening system that can simultaneously analyze 24 bacterial target genes using multiplex real-time SYBR Green polymerase chain reaction (SG-PCR). This screening system, named Rapid Foodborne Bacterial Screening 24 (RFBS24), includes 8 sets of multiplex real-time SG-PCR assays, with each set comprising 4 primer pairs for 3 target genes and an internal amplification control (IAC).…”
Section: Introductionmentioning
confidence: 99%
“…RFBS24 can identify foodborne pathogens more quickly than traditional methods can, thus leading to quicker dissemination of relevant information to public health officials. Nonetheless, Fukushima et al (6) reported that the detection limit of RFBS24 for Salmonella spp. is worse than that for other pathogens and that identification of some bacterial pathogens is difficult due to small differences in melting temperatures (T m ) of PCR products between some target genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation